Intra-subject variability in the auditory brainstem response using a vertical montage recording - Dzulkarnain, Ahmad Aidil Arafat; Sulaiman, Nur Hafizah; Buyong, Ainoor Shafinas (Maney Publishing, 2014)
Purpose